Sources of current account fluctuations in industrialized countries - Aikaterini Karadimitropoulou; Miguel A. León-Ledesma (University of Kent, Department of Economics, 2009)
We analyze the sources of current account fluctuations for the G6 economies. Based on Bergin and Sheffrin's (2000) two-goods inter-temporal framework, we build a SVAR model including the world real interest rate, net output, real exchange rate, and the current account. The theory model allows for the identification of structural shocks in the SVAR using longrun restrictions. Our results suggest three main conclusions: i) we find evidence in favour of the present-value model of the CA for all countries except France; ii) there is substantial support for the two-good intertemporal model, since both external supply and preferences shocks account for an important proportion of CA fluctuations; iii) temporary domestic shocks account for a large proportion of CA fluctuations, but the excess response of the CA is less pronounced than in previous studies.
Keywords: F32; F41; 330; current account; real exchange rate; two-good intertemporal model; SVAR; Zahlungsbilanzungleichgewicht; Volatilität; Wechselkurs; Schock; VAR-Modell; Industriestaaten